Experimental investigations of a combustion chamber pre-diffuser. (12th May 2004) - Becker, B.; Stoffel, B.
The flow in gas turbines is characterised by a high level of non uniformities due to combustion effects and instabilities of the surrounding turbomachines. It is assumed that the wakes issuing from the upstream axial compressor interact with the combustion process in the flame tube. The diffuser which is positioned between the compressor and the flame tube is of particular importance for the inlet flow conditions of the combustion. This paper is concerned with the characterisation of the flow field in and at the exit of the pre-diffuser. Experimental investigations have been done to get information about the flow behaviour in the diffuser. All measurements have been acquired using a modelled annular combustion chamber test facility with a simulated one stage axial compressor in front of it.